Pendidikan Islam dan Tantangan The Great Shifting di Era Pandemi Covid-19 - Maharani, Dewi; Akmalia, Rizkha Diana; Faradilla, Gita Yuniar (Fakultas Tarbiyah, Institut PTIQ Jakarta, 2021)
This article was written to explain the strategic relationship between Islamic Education in facing changes in the Covid-19 pandemic era, how Islamic education, which in quantity shows progress, but in terms of quality is still questionable, it can be seen from the output of Islamic Education Institutions in taking employment opportunities in the country. alone is still far from people's expectations, this problem was exacerbated by the emergence of the Covid-19 pandemic which changed the technology-based education system. This study uses a qualitative approach with descriptive analysis, while the data collection technique is in the form of documentation which is then analyzed. The results of the study show that the strategies carried out in developing Islamic Education in the face of Covid-19: First, Having a Second Morality Commitment, Outcome of Skills and Expertise, Third, Mastering Science, Technology and Innovative Ability, Fourth, Collaborating with stakeholders and foreign institutions.